Five-Year Retrospective Analysis of Superficial Fungal Infections: Insights from Hospital Experience - Nikoleta Đorđevski; Elizabeta Ristanović; Ana Ćirić; Diana Tomić; Biljana Nikolić; Nemanja Rajčević; Dejan Stojković (Journal of Fungi)
This study aimed to assess the incidence and distribution of dermatomycetes in patients at the Medical Military Academy (MMA) with suspected superficial skin infections over a five-year period (October 2017 to October 2022) and to analyze variations in fungal infections based on factors such as gender, body part, and time, particularly influenced by the COVID-19 pandemic. A total of 3993 samples were analyzed. Collected data were statistically analyzed with two tests. A total of 1048 samples were positive for fungal infections. Over the study period, Trichophyton mentagrophytes and Trichophyton rubrum were the predominant taxa, while Microsporum canis and Candida albicans were frequently observed. Statistical analysis indicated significant annual variations for T. mentagrophytes, T. rubrum, and M. canis, with monthly differences for T. mentagrophytes in June and August and M. canis in October and December. Gender-based analysis showed that T. rubrum and T. mentagrophytes were more common in males, while M. canis, C. albicans, Candida spp., and Geotrichum candidum were more prevalent in females. Analysis by body part revealed that Trichophyton rubrum and Microsporum canis showed significant differences between surface types. These findings can help improve diagnostic, therapeutic, and preventative strategies.